Xeroradiographic techniques applied to assessment of Achilles tendon in inflammatory or metabolic diseases. Issue 6 (December 1975) - Gerster, J C; Hauser, H; Fallet, G H
Abstract : Ten patients with inflammatory disease (rheumatoid arthritis, ankylosing spondylitis, Reiter's disease) or metabolic disease (gout, pseudogout, tendinous xanthomatosis) affecting the Achilles tendons are presented and discussed. Radiological lateral views of heel were obtained with xeroradiographic techniques, which permitted the recording on the same image of details of both bone and soft tissue and the evaluation and quantification of the changes in the Achilles tendons. Xeroradiography seems to be a very suitable radiological technique for routine use in the evaluation and follow up of rheumatic diseases of the foot.